Organizational maturity and projects performance: The mediation of benefits management - Romão, M.; Carvalho, H.; Caldeira, M.; Gomes, J. (WEBIST 2014: Proceedings of the 10th International Conference on Web Information Systems and Technologies, 2014)
Nowadays the investments made by organizations to get better business performances are crucial and difficult to obtain. So, it́s more and more important that the business-cases underline not only the shortterm objectives, but also the long-term benefits that promotes a sustainable future for organizations and investors. The main objective of our research is to study how investments on IS/IT influence projects performance in organizations. The rational of our model is that organizational maturity has a positive effect on projects performance with the mediation of benefits management. We emphasize that the integration between a maturity model and a benefits management approach can increase the effectiveness of strategic projects. Besides, it can also improve business confidence that the investments done match the desired maturity stages and will then collect benefits perceived as business value.